2023
DOI: 10.1371/journal.pgph.0001605
|View full text |Cite
|
Sign up to set email alerts
|

Culturally adapting a mindfulness and acceptance-based intervention to support the mental health of adolescents on antiretroviral therapy in Uganda

Abstract: The dual burden of living with HIV and negotiating life stage changes has been identified as a contributing factor to lapsed adherence among adolescents with HIV in sub-Saharan Africa. While psychosocial support can promote medication adherence, most interventions in use with adolescents were originally developed for the general population creating a gap in appropriate support. Life-stage-appropriate, evidence-based psychosocial support interventions have been used with young people in high-income contexts, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 61 publications
1
7
0
Order By: Relevance
“…43 45 Moreover, the results concur with studies that found improved levels of psychological flexibility among adolescents who were exposed to DNA-v training. 42 , 67 By improving psychological flexibility among AWH, our results confirm that MABIs are transdiagnostic and can address a range of emotional and behavioral challenges across conditions. 70 …”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…43 45 Moreover, the results concur with studies that found improved levels of psychological flexibility among adolescents who were exposed to DNA-v training. 42 , 67 By improving psychological flexibility among AWH, our results confirm that MABIs are transdiagnostic and can address a range of emotional and behavioral challenges across conditions. 70 …”
Section: Discussionsupporting
confidence: 58%
“…Mindfulness and acceptance-based interventions (MABIs) have the potential to promote self-regulation, resilience, and self-acceptance among young people 41 , 42 through a mechanism called psychological flexibility, the ability to live consciously aware of life challenges but deliberately making choices that are personally meaningful. 43 45 MABIs, through targeting psychological flexibility, address cognitive fusion (a state where individual behaviors are dominated by particular thoughts) and experiential avoidance (obsessing about suppressing negative thoughts), 41 , 46 processes that can impact adherence to medication among young people.…”
Section: Introductionmentioning
confidence: 99%
“…To implement these adaptations, sessions one and two (Introduction and Discoverer) were merged into a single session and the same was done for sessions five and six (Values and Self as context). To reduce session time with the adapted schedule, we replaced lengthy narratives from the DNA-V manual with shorter plays and games carrying the same messages [31]. This adaptation was reviewed and approved by the developers of the DNA-V.…”
Section: Protocol and Adaptationmentioning
confidence: 99%
“…The DNA-V intervention is a flexible mental health support program that targets to promote psychological flexibility among young people and can be delivered by lay providers such as counsellors and adolescent peers with minimal experience in facilitating group psychotherapy and working with adolescents. The providers are trained in using the DNA-V manual, practicing mindfulness, creating present moment awareness, values clarification and facilitating experiential exercises [30,31] and adherence to the guides of the manual ensures fidelity. In this study, group sessions of the DNA-V were delivered to AWH as life skills training responding to the developmental needs of young people [29].…”
Section: Study Interventionmentioning
confidence: 99%
See 1 more Smart Citation